2007
DOI: 10.1291/hypres.30.249
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminocyclopropanecarboxylic Acid, an Antagonist of N-Methyl-D-Aspartate Receptors, Causes Hypotensive and Antioxidant Effects with Upregulation of Heme Oxygenase-1 in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: 1-Aminocyclopropanecarboxylic acid (ACPC) has been shown to protect neurons against glutamate-induced neurotoxicity by reducing N-methyl-D-aspartate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…54 According to the previous report, 1-aminocyclopropane carboxylic acid improves inflammation by inhibiting the expression of neuronal nitric oxide synthase (nNOS) and endothelial nitric oxide synthase (eNOS), elevating the expression of heme oxygenase-1 (HO-1) and the activity of SOD. 55 In addition, dulcitol, inosine, equol, fluoxetine, linoleoyl ethanolamide, evodiamine, riboflavin and taurocholate had also been reported to exert a broad range of anti-inflammatory and immunomodulatory effects, including inhibiting proinflammatory cytokine and chemokine production, promoting anti-inflammatory cytokine production, and altering the inflammation-related signaling pathways. 56–59 A previous study had shown that excessive alcohol consumption induced a significant increase in the level of proinflammatory factors, resulting in liver inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…54 According to the previous report, 1-aminocyclopropane carboxylic acid improves inflammation by inhibiting the expression of neuronal nitric oxide synthase (nNOS) and endothelial nitric oxide synthase (eNOS), elevating the expression of heme oxygenase-1 (HO-1) and the activity of SOD. 55 In addition, dulcitol, inosine, equol, fluoxetine, linoleoyl ethanolamide, evodiamine, riboflavin and taurocholate had also been reported to exert a broad range of anti-inflammatory and immunomodulatory effects, including inhibiting proinflammatory cytokine and chemokine production, promoting anti-inflammatory cytokine production, and altering the inflammation-related signaling pathways. 56–59 A previous study had shown that excessive alcohol consumption induced a significant increase in the level of proinflammatory factors, resulting in liver inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In adult SHR, previous studies have demonstrated that both acute and chronic administration of an HO-1 inducer normalizes blood pressure. The normalization by 1-aminocyclopropanecarboxylic acid (ACPC) of blood pressure elevation and the reduced mortality to stroke was reported to involve induction of HO-1, resulting in antioxidant and vascular relaxation effects, in stroke-prone SHR (Gao et al, 2007). Heme administration decreased blood pressure in SHR (Abraham and Kappas, 2008; Levere et al, 1990; Botros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was interesting to notice that HMOX1 is not induced by AG in AGS cells. Indeed, many reports have demonstrated that several antioxidants suppress cellular damages through the induction of HMOX1 (36,37). Since HMOX-1 acts as a molecular anti-oxidant, it can also be imagined that AG protects AGS cells from H 2 O 2 through the induction of HMOX-1 gene.…”
Section: Discussionmentioning
confidence: 99%